Ongoing teacher training for the education on ethnic-racial relations: an analysis over a state practice (Research, Society and Development, 2022)
The study aims at analysing ongoing training practices which focus on preparing the teachers to deal with the teaching content of history, and Afro-Brazilian and African culture (THAAC). In terms of methodology, it addresses the analysis of stablished trainings, lesson plans and a set of focal groups, in which teachers and principals participated, that took place in four public schools in Acre. The results show that the search for technical solutions stablishes the phase of a new management of pedagogical practices and, in this case, THAAC is reduced to the abilities proposed by the logic of the Secretary of Education. That shows some kind of political staging committed to the logic which is external to the school. The speeches of the agents, instead of stating the autonomy of the teachers, point a path stablished by the routine imposed by the administration, with highly driven planning, which leads them to a dependence of externally set imperatives. The school agents developed a type of cultural professionalism which must pay obedience to exogenous generated rules. That makes their professionalism be measured up by performances in which the teaching practices are more and more shaped to answer to the new external demands which, in turn, compromises the function of the school and the possible re-education of ethnic-racial relations.